Indonesia’s Global Maritime Fulcrum: Contribution in the Indo-Pacific Region - Mohd Agoes Aufiya (Department of International Relations, Universitas Andalas, 2017)
This research attempted to analyse the effectiveness of the new policy under the President Joko Widodo (Jokowi) which is called as “Global maritime fulcrum” or poros maritim dunia as approach in contributing Indo-Pacific region stability. The policy has strong maritime sense linkages inspired by Indonesia’s past maritime kingdom such as Majapahit and Sriwijaya glory, hence the new government try to revive the maritime identity in the nation-state to achieve national interest not only for domestic development but importantly also for stability in the region. As the relatively new policy at the time, the research try a preliminary assessment within two years of Jokowi administration. The effectiveness of this policy will be assessed no how the policy were implemented dan responded to deal with challenges in the Indo-Pacific region including the domestical sphere. The discussion will be followed with the concluding remarks for suggestion on the policy including evalutions as well as recommendations. Key Words: Maritime, Indo-Pacific, Indonesia, Joko Widodo, Global Maritime Fulcrum (GMF),Sea Toll.